Faktor yang Berhubungan dengan Deteksi Dini Kanker Serviks Metode IVA di Puskesmas Kota Padang - Miftahil Fauza; Aprianti Aprianti; Azrimaidalisa Azrimaidalisa (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: In 2013 the prevalence of cervical cancer in West Sumatra was 0.9 per 1000 population. This data exceeds the Indonesian prevalence of 0.8 per 1000 population.  Lack of public knowledge regarding early detection of cervical cancer is the cause of the high prevalence of cervical cancer. This study aims to determine the factors associated with the participation of women of childbearing age in the early detection of VIA method cervical cancer in Padang City Health Center in 2018.Method: This study was a cross sectional design, conducted from February to October 2018. The population was women who visited the Alai Health Center and Pegambiran Health Center with a total sample were 110 respondents. The sampling method uses consecutive sampling method. Data collection by interview using a questionnaire. Data were analyzed by Chi-square statistical test and logistic regression with 95% confidence degree.Result: The results showed that 60% of respondents had never done the early detection of VIA cervical cancer method. Statistical test results show there was a significant relationship between the level of knowledge (p = 0,000), attitude (p = 0,041), access to information (p = 0,000) and husband's support (p = 0,000) with the early detection of VIA cervical cancer method. The results of multivariate analysis showed that the most dominant variables affected the participation of women in early detection of cervical cancer, namely husband's support (p = 0,000) and POR = 46,693.